2015
DOI: 10.3389/fncel.2015.00280
|View full text |Cite
|
Sign up to set email alerts
|

A delicate balance: role of MMP-9 in brain development and pathophysiology of neurodevelopmental disorders

Abstract: The extracellular matrix (ECM) is a critical regulator of neural network development and plasticity. As neuronal circuits develop, the ECM stabilizes synaptic contacts, while its cleavage has both permissive and active roles in the regulation of plasticity. Matrix metalloproteinase 9 (MMP-9) is a member of a large family of zinc-dependent endopeptidases that can cleave ECM and several cell surface receptors allowing for synaptic and circuit level reorganization. It is becoming increasingly clear that the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
198
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(209 citation statements)
references
References 144 publications
(305 reference statements)
3
198
0
8
Order By: Relevance
“…By contrast, the Drosophila genome encodes just one secreted Mmp (Mmp1), one membrane Mmp (GPI-anchored Mmp2) and one secreted Timp. In lieu of mammalian studies, which show that extracellular proteases play central roles determining synapse structure, function and number (reviewed in Reinhard et al, 2015;Shinoe and Goda, 2015;Wójtowicz et al, 2015), we took advantage of the reductionist Drosophila model to genetically dissect the complete, integrated mechanism of the matrix metalloproteome in synaptic development.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the Drosophila genome encodes just one secreted Mmp (Mmp1), one membrane Mmp (GPI-anchored Mmp2) and one secreted Timp. In lieu of mammalian studies, which show that extracellular proteases play central roles determining synapse structure, function and number (reviewed in Reinhard et al, 2015;Shinoe and Goda, 2015;Wójtowicz et al, 2015), we took advantage of the reductionist Drosophila model to genetically dissect the complete, integrated mechanism of the matrix metalloproteome in synaptic development.…”
Section: Introductionmentioning
confidence: 99%
“…The MMP-9 gene has functions in embryonic development, reproduction, tissue remodeling, carcinogenesis, and metastasis (12,27,35). Moreover, to date, many MMP-9 related polymorphism studies have been performed to clarify its role in different steps of carcinogenesis in various cancer types including colorectal, gastric, head and neck carcinomas, renal cell cancer, endometrium carcinoma, prostate cancer, oral cavity carcinoma, breast cancer, malignant melanoma, nasopharynx cancer, and esophagus cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These studies provide an avenue for possible therapeutic treatments in a range of neurological disease states with elevated Mmp activity (Hadler-Olsen et al, 2011;Reinhard et al, 2015). In particular, Mmp hyperactivity has been causally implicated in FXS and related ASD conditions (Abdallah and Michel, 2013;Dziembowska et al, 2013;Sidhu et al, 2014;Siller and Broadie, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Improper Mmp expression and activity is implicated in a range of neurological disorders, including schizophrenia (Lepeta and Kaczmarek, 2015), addiction (Liu et al, 2010), epilepsy (Pollock et al, 2014) and autism spectrum disorder (ASD) (Abdallah and Michel, 2013). As the most common heritable ASD and intellectual disability, Fragile X syndrome (FXS) underscores the importance of preserving Mmp balance to control proper synaptic structure and function (Reinhard et al, 2015;Siller and Broadie, 2011). Importantly, the Mmp inhibitor minocycline alleviates synaptic and behavioral phenotypes in FXS disease models (Bilousova et al, 2009;Broadie, 2011, 2012), and has shown promise in clinical trials for human patients , showing that elevated Mmp activity is causally linked to FXS neuropathology (Doll and Broadie, 2014).…”
Section: Introductionmentioning
confidence: 99%